Analysis of the determinants influencing the choice of local market garden crops: tomato, chili, onion, krinkrin, and okra in Southern Benin - Adjobo, Olouhitin Mouléro Franck Ronald (European Scientific Journal, ESJ, 2025)
For over two decades, Benin has experienced a steady rise in market gardening production. However, this growth has not translated into self-sufficiency, as the country continues to rely on imports from neighboring nations during lean seasons. Analyzing the factors influencing the choice of local market garden crops could provide valuable insights for addressing this issue. This study employed a multivariate probit model to identify the determinants influencing the adoption of specific market garden crops, namely tomato, pepper, onion, krinkrin, and okra, on farms in southern Benin. The research was conducted using a randomly selected sample of 474 market gardeners. Findings revealed interdependence and complementarity in the adoption of the various crops studied. Notably, most surveyed producers preferred adopting combinations of either two (27.43%) or four (25.74%) crops at a time. Moreover, key factors influencing crop adoption included the presence of a local market, the farmers’ level of education, access to a telephone network, the nature of the area, particularly its proximity to the water table, and the security of farming sites.